2018
DOI: 10.3389/fnbeh.2018.00012
|View full text |Cite
|
Sign up to set email alerts
|

Aggression Profiles in the Spanish Child Population: Differences in Perfectionism, School Refusal and Affect

Abstract: The aim of this study was to identify the existence of combinations of aggression components (Anger, Hostility, Physical Aggression and Verbal Aggression) that result in different profiles of aggressive behavior in children, as well as to test the differences between these profiles in scores of perfectionism, school refusal and affect. It is interesting to analyze these variables given: (a) their clinical relevance due to their close relationship with the overall psychopathology; and (b) the need for further e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 69 publications
4
10
0
2
Order By: Relevance
“…These results confirm the second hypothesis which anticipates that the adolescents with a high SRB profile would have higher scores in cyberbullying and reinforces the findings of prior studies that found cybervictimized adolescents to be a population at risk of not attending school because they did not feel safe (Steiner and Rasberry, 2015; Grinshteyn and Yang, 2017) and in order to engage in escape and avoidance behavior in an educational context (Barboza, 2015). Furthermore, the results are in line with those from other studies with adolescents that have related the level of absenteeism and school rejection with being an aggressor or perpetrator of cyberbullying (Wright, 2015; Morin et al, 2018), and high aggression levels with higher levels of school rejection in order to avoid negative affectivity and social evaluation and to gain the attention of significant others and similar levels of school rejection to obtain tangible reinforcers (Vicent et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…These results confirm the second hypothesis which anticipates that the adolescents with a high SRB profile would have higher scores in cyberbullying and reinforces the findings of prior studies that found cybervictimized adolescents to be a population at risk of not attending school because they did not feel safe (Steiner and Rasberry, 2015; Grinshteyn and Yang, 2017) and in order to engage in escape and avoidance behavior in an educational context (Barboza, 2015). Furthermore, the results are in line with those from other studies with adolescents that have related the level of absenteeism and school rejection with being an aggressor or perpetrator of cyberbullying (Wright, 2015; Morin et al, 2018), and high aggression levels with higher levels of school rejection in order to avoid negative affectivity and social evaluation and to gain the attention of significant others and similar levels of school rejection to obtain tangible reinforcers (Vicent et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…(e.g., Morris & Lomax, 2014). There is a limited, yet growing interest in the understanding of how this personality trait may affect certain externalizing problems, such as aggressive behavior (e.g., García-Fernández, Vicent, Inglés, Gonzálvez, & Sanmartín, 2017;Stoeber, Noland, Mawenu, Henderson, & Kent, 2017;Vicent, Inglés, Sanmartín, Gonzálvez, & García-Fernández, 2018).…”
mentioning
confidence: 99%
“…Moreover, to our knowledge, with the exception of the works of Stoeber et al (2017) and Vicent et al (2018), no prior studies have jointly considered the three components of aggressive behavior. That is, previous studies have only focused on hostility and anger.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should consider the need to design and offer educational strategies with specific intervention and prevention measures for use by schools and education specialists ( Bucur et al, 2020 ). Preventive interventions could be focused on improving the affective levels of all students, especially the most emotionally vulnerable, which would be positively reflected in the development and happiness of the students due to the relationship found between the school refusal behavior, affectivity, and aggression ( Sanmartín et al, 2018 ; Vicent et al, 2018 ). Designing these proposals, the different reasons for school refusal must be taken into account in order to offer a more adjusted intervention.…”
Section: Discussionmentioning
confidence: 99%